Corruption risks in higher education institution (Journal of actual problems of jurisprudence, 2021)
The article examines some corruption risks that exist in the field of higher education in Kazakhstan. Currently, the identification of corruption risks in the activities of higher education institutions is one of the most effective mechanisms to prevent the occurrence of corruption in the field of education. In this regard, the anti-corruption authorities in the Republic of Kazakhstan pay special attention to this problem. The paper provides examples of ongoing activities initiated by both state bodies: the Ministry of Education and Science of the Republic of Kazakhstan, the Anti-Corruption Agency of the Republic of Kazakhstan (carried out by departments of the Anti-Corruption Service), and higher education organizations and their associations (the League of Academic Integrity), as well as public associations registered on the territory of the state, which contribute to the identification of corruption risk factors. A brief description of certain types of corruption risks in the field of higher education is given. Among them: low wages, violations in the distribution of state grants, non-compliance with the principles of academic integrity. Proposals have been developed to reduce corruption risks, as a result of which the factors of corruption risk will be minimized, which will lead to the elimination of corruption in higher education institutions.Key words: corruption risks, corruption, higher educational institutions, Sanaly urpak, academic integrity, salary, state grant, teacher, student.